Awareness, Challenges and Measures for Lean Construction Implementation Amongst Malaysian Grade 7 (G7) Contractors - Sim Nee, Ting; Yong Siang, Lee; Chee Khoon, Ng; Dahlia, Jara’ee (Construction Research Institute of Malaysia (CREAM), 2025)
Lean Construction, derived from Lean Manufacturing, offers a systematic approach to minimizing waste, improving process efficiency, and enhancing project delivery for the construction sector. However, its adoption remains limited in Malaysia. This study examines the implementation of Lean Construction practices among Grade 7 (G7) Contractors, focusing on the awareness and challenges towards the concept and strategies for improvement. A quantitative survey was conducted and 122 construction personnel from G7 contractors’ firms responded. Findings reveal a rather strong awareness of Lean principles among respondents especially on the operational efficiency and waste reduction benefits. However, knowledge gaps persist in client-centered principles such as Value Identification and Value Stream Identification, which are crucial for aligning projects with customer needs. Top barriers to implementation of Lean Construction techniques include insufficient awareness of the actual practices, lack of top management support and limited commitment from project teams. Strong management leadership and investment in modern technologies emerge as the most critical factors for facilitating Lean Construction implementation. Additionally, raising awareness through education and training, empowering construction personnel, and conducting pilot projects are essential for successfully integrating Lean techniques into projects. Given the persistent challenges in the construction sector, including dealing with inefficiencies, project delays, cost overruns and material wastages, this study offers critical insights into the role of Lean Construction in addressing these issues. By identifying key barriers and effective implementation strategies, the findings contribute to a deeper understanding of how Lean principles can enhance productivity and promote a more sustainable construction industry in Malaysia.